ASSESSING PRESERVICE ENGLISH TEACHERS’ METACOGNITIVE AWARENESS AND ITS RELATION TO THEIR TEACHING PERFORMANCE - Wahyuni, Sri; Al-Awawdeh, Nabil; Aini, Nurul (Universitas Muhammadiyah Metro, 2026)
Metacognition becomes one of the most psychological concepts and the important domain in any teaching and learning process. It is assumed that students with high level of metacognitive awareness tends to have high academic achievement. However, the relation of metacognitive awareness and teaching performance of pre-service teachers are still questionable. This study aims at investigating the preservice English teachers’ metacognitive awareness and its relation to their teaching performance in UIN Syekh Wasil Kediri. By employing correlational research design, thirty-three preservice English teachers joined this study. Metacognitive awareness inventory (MAI) adopted from Schraw and Dennison (1994) was used to collect the data on metacognitive awareness level, and teaching practicum checklist to evaluate teaching performance. In analyzing the data, descriptive statistics and Pearson Bivariate correlation analysis through SPSS were used. The finding shows that there was no significant relationship between metacognitive awareness and teaching performance of preservice English teachers. The significant value obtained was higher than the significant level (0.557 > 0.05). Furthermore, when both types (metacognitive knowledge and metacognitive regulation) were analyzed separately, there was no significant relationship between metacognitive knowledge and teaching performance (.532 ˃ .05), and between metacognitive regulation and teaching performance (.584 ˃ .05. It implied that metacognitive awareness may not become the main determinant factor in teaching performance of preservice English teachers; other factors such as linguistics competence may influence more on teaching performance.